2012
DOI: 10.4028/www.scientific.net/amr.488-489.46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water as Non-Solvent Additive on Performance of Polysulfone Ultrafiltration Membrane

Abstract: Abstract. In this work, polysulfone ultrafiltration membranes were prepared via simple phase inversion with distilled water as non-solvent additive. The main reason for the addition of water in polysulfone dope solution preparation was to enhance the membranes structure. In the dope, 15 wt. % of polysulfone was used and water was varied up to 6 wt. %. The effects of water on morphology, porosity and tensile properties were investigated in detail. From the porosity test, results showed that the addition of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…This straight or longer finger-like structure formed at the bottom give better permeation compared to short finger-like structure [7]. In fact, by increasing the RHS content, the pore at the top layer membrane become smaller.…”
Section: Applied Mechanics and Materials Vol 372mentioning
confidence: 94%
See 1 more Smart Citation
“…This straight or longer finger-like structure formed at the bottom give better permeation compared to short finger-like structure [7]. In fact, by increasing the RHS content, the pore at the top layer membrane become smaller.…”
Section: Applied Mechanics and Materials Vol 372mentioning
confidence: 94%
“…The addition of small amount of additive into casting solution can lead to significant changes to the characteristic and performance of membrane [4,5,6]. It is reported that additives can affect the final membrane characteristic either by changing the solvent capacity or by changing phase separation kinetic and thermodynamic mechanism [7,8]. The additive have tendency to enlarge macrovoids formation which then improve the interconnectivity of the pores and resulting in higher porosities in the top layer and sub layer [9].…”
mentioning
confidence: 99%
“…Later on, The casting solution was cast using casting knife with range thickness 100-120µm and immersed into a coagulation bath containing distilled water. Then, the flat sheet membranes were dried 24 h before testing [1,2,3,11]. In this study, the coagulation medium were demineralized water or aqueous solution of sodium chloride (NaCl) at dissimilar concentrations is modified repeatedly in the range of 1-5 %.…”
Section: Preparation Of Psf Ultrafiltration Membranementioning
confidence: 99%
“…Thus, modification of basic procedure are commonly required including the addition of certain additive [1][2][3][4][5], introducing advance stride to make enhancement such as evaporation [9] or annealing [10], and coupling chemical reaction with phase separation [11]. Previous studies reported that by modification of polysulfone (PSf) ultrafiltration membrane with changing composition in casting solution or coagulation bath will gives positive implication to morphology and properties of membrane [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation